Migrations and the deepening of the socio-environmental crisis - Ruiz Agudelo, César Augusto (Universidad Distrital Francisco José de Caldas, 2018)
Migrations are massive phenomena that figure humanitarian crises on a global scale, which, in a transversal perspective, go beyond the matter of labor, civil or social rights. In this article, this phenomenon is reviewed from the following perspectives: 1) - Migrations as a cause and consequences of political and social crises. 2) - Migrations as a cause and consequences of environmental crises. The aforementioned related to the fact that this phenomenon can deepen the global socio-environmental crisis, which nowadays is perceived with greater intensity. Controlling and managing migratory flows is a "transversal" challenge that involves the recognition of our environmental values.